Comparative Burden of HbA1c and RBG Levels Among Individuals Above 25 Years in the Post-COVID-19 and Pre-COVID-19 Periods: A Retrospective Analysis at a Medical College Hospital, Ramanagara, Karnataka : Impact of COVID on RBG levels - Kunjathur, Shilpashree Madhava; Shivanna, Akshitha; Leelambika (Indian Journal of Community Health, 2025)
Introduction The COVID-19 pandemic significantly impacted public health, including metabolic health and glycemic control. SARS-CoV-2 affects glucose metabolism through inflammation, stress, and healthcare disruptions. HbA1c, a key diabetes marker, has shown increased levels post-COVID, suggesting higher hyperglycemia burden. In India, pre-COVID data revealed 12% of women and 14% of men over 15 years had RBG >140 mg/dl, with higher rates reported during COVID due to stress, inflammation, and treatment changes like corticosteroid use. We hypothesized a 15% rise in elevated HbA1c and RBG levels post-COVID among patients over 25 years. This study compared pre- and post-COVID trends by age and gender. Methods: The study was conducted at CDSIMER Hospital, as a retrospective observational analysis of HbA1c and RBG levels in patients aged >25 years. Two periods were compared: Pre-COVID-19 (2019–2021) and Post-COVID-19 (2022–2023). Data from the Laboratory Information System (LIS) and NFHS-5 reports were analyzed. Inclusion criteria included complete HbA1c and RBG records. The estimated sample size, based on previous studies, was 10,475. Results: A total of 17,238 patients data were analysed. In the post-COVID period, 16.95% had very high levels (?160 mg%), more than doubling from NFHS-5 data. Males showed a higher prevalence (22.15%) than females (12.86%). HbA1c >6.5% was found in 64% of individuals aged >25 years. Conclusion: Alarming increase in blood glucose levels among population aged above 25 years. National Health Programmes to take justifiable action on priority.